CAN THE TRANSFORMATION OF INSTRUCTION PROCESS INTO A VIRTUAL PLACE INDUCE A SHIFT IN BEHAVIORAL PATTERNS OF TEACHERS AND STUDENTS? - Ljajko, Eugen; Stojanović, Vladica; Valjarević, Dragana; Jovanović, Tanja (Bulletin of Natural Sciences Research, 2016)
The goal of this study is to reveal possible influence that the participants’ age and Information and Communications Technologies (ICT) usage in the instruction process can have on behavior that defines whether students and teachers belong to one of the Digital Native/Immigrant or Visitor/Resident groups. We collected data through two surveys that covered a total of 1273 students and 382 teachers from southern regions of Serbia. The surveys consisted of questions about availability of computers and internet, ICT use in the instruction process, and communication habits in the ICT-empowered instruction process. The first survey covered both, students and teachers that were involved in the instruction process mostly deprived of the ICT usage. The second survey covered participants of an instruction process that was successfully improved by an ICT usage. Data analysis shows a shift in communication patterns of teachers and a sharp improvement in computer use for educational purposes for both groups included in the surveys. The change is induced by a proper ICT usage in the instruction process. Conclusions that followed the data analysis lead us to better approaches in organizing ICT usage in the instruction process that enable participants fully employ their resources in order to improve teaching techniques and learning.